Professional English for Electrical Power Engineering. Part 4 электронный курс - Andreev, M. V. specialist in the field of electric power engineering Associate Professor of Tomsk Polytechnic University, Candidate of technical sciences 1987- (TPU Moodle, 2021)
Целью данного курса является изучение теоретических и практических аспектов работы электроэнергетических систем, профессиональной терминологии, повышение навыков владения английском языком.